2010
DOI: 10.1243/13506501jet765
|View full text |Cite
|
Sign up to set email alerts
|

The influence of antiwear additive concentration on the tribological behaviour of a-C:H:W/steel tribosystem

Abstract: The effect of antiwear (AW) commercial additive concentration on the load-carrying capacity (scuffing resistance) of a-C:H:W/steel tribo-system intended for heavy-loaded machine parts was investigated. For comparison, steel/steel contacts were also investigated. The scuffing resistance has been measured as the limiting pressure of seizure ( poz) using the four-ball apparatus. The method with continuously increasing load was applied. The tribo-systems were lubricated with poly-alpha-olefin as base oil mixed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…As shown in Figure 3C, the peak at 706.3 eV attributes to Fe δ + in bulk Fe 2 P and hybrid Fe 2 P, [23] demonstrating the presence of Fe 2 P. The other peak at 713.4 eV is assigned to Fe bound to phosphate. [24] From the P 2p peak ( Figure 3D), the typical peak at 129.4 eV is assigned to P δÀ species in metal phosphide. [25] The other binding energy of 133.8 eV can be associated with P in phosphates.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 3C, the peak at 706.3 eV attributes to Fe δ + in bulk Fe 2 P and hybrid Fe 2 P, [23] demonstrating the presence of Fe 2 P. The other peak at 713.4 eV is assigned to Fe bound to phosphate. [24] From the P 2p peak ( Figure 3D), the typical peak at 129.4 eV is assigned to P δÀ species in metal phosphide. [25] The other binding energy of 133.8 eV can be associated with P in phosphates.…”
Section: Resultsmentioning
confidence: 99%
“…Because the potential market for ecological lubricants seems to be wide and because new EU regulations imposing the application of biodegradable lubricants in selected areas of technique can be expected, many researchers have undertaken an effort to develop ecological lubricants. They include ecological oils, greases and cutting fluids; however, there is also a new approach related to the reduction of the content of toxic additives in lubricants by the application of scuffing‐preventive hard, thin coatings on the mating machine parts …”
Section: Introductionmentioning
confidence: 99%
“…They include ecological oils, greases and cutting fluids [3][4][5][6][7] ; however, there is also a new approach related to the reduction of the content of toxic additives in lubricants by the application of scuffing-preventive hard, thin coatings on the mating machine parts. 8 The aim of this work was to assess natural and white oils as potential candidate bases of gear oils. To this end, scuffing tests, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was also reported that WC/C coatings exhibit excellent behaviour under heavily loaded conditions of sliding and rolling contact (Krantz et al, 2003). Many efforts have been made in recent years to understand the lubrication of coated components (Michalczewski et al, 2009;Vlad et al, 2010;Podgornik et al, 2005;Madej et al, 2006;Kula et al, 1997). Despite many papers concerning this topic, the wear mechanism under scuffing conditions of coated parts is far from a complete explanation.…”
Section: Introductionmentioning
confidence: 99%